Social history today through the analysis of Hobsbawm's historical writing - Coşkun, Çiğdem. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 2002., 2002)
This thesis aims at concentrating on the main discussions in historiography in the last quarter of the twentieth century with regard to the changing questions and problems such as what the position of historian when s/he writes is, whether it is possible to speak of historical reality or not- through the analysis of the way in which an individual historian views and tries to solve them. There are two overlapping dimensions of the thesis in this sense: On the one hand, the thesis examines the place and evolution of social history within historiography, and its position, especially after the 1980s, against the historical trends let us say, postmodernist- seeming to threaten not only social history in particular but history as a 'legitimate cognitive enterprise' in general. On the other hand, it takes into consideration how E. J. Hobsbawm writes history as a social historian (with an emphasis on the works exemplifying his main slant of interests and his way of writing history) and how he views it (with an emphasis on his considerations on historical writing and the different historical trends within it). In relation with the analysis of his works, subsequently, it discusses the position of social history and history in general- within the framework of the arguments over the validity of the challenges towards it.
Keywords: Social history.; Social problems -- History